Reafirmasi Posisi Dai dalam Dakwah Kolaboratif di Era Global - Syukri Syamaun (Sadida Islamic Communications and Media Studies, 2025)
This article aims to discuss the position of dai in the global context by examining their roles, challenges, and strategies for effective da'wah. Drawing from scholarly literature and case studies, this study highlights the importance of dai as educators, mediators, and community leaders. This article uses a qualitative approach through a "systematic literature review" and case study analysis of contemporary da'wah practices. The article concludes that the reaffirmed position of dai in collaborative da'wah is indispensable for promoting peaceful coexistence, strengthening islamic identity, and contributing to global harmony